Gestational age at birth, birth weight, and gestational age when intrauterine brain sparing occurs determines the neonatal outcome in growth-restricted infants born before 32 weeks of gestation: a retrospective cohort analysis - Köber, Franziska; Heimann, Yvonne; Lehmann, Thomas; Schleußner, Ekkehard; Proquitté, Hans; Groten, Tanja (Frontiers in Pediatrics, 2024)
Background Preterm birth and fetal growth restriction are the main determinants of perinatal mortality. In the absence of therapeutic interventions, management is restricted to the observation of fetal growth and fetoplacental perfusion to determine the timing of delivery. Fetal circulatory redistribution, known as “brain sparing,” represents a sign of fetal hypoxia and has been implemented in algorithms for when to deliver. In the absence of any other option, the nitric oxide donor pentaerythrityl tetranitrate (PETN), which has been shown to improve fetoplacental flow and reduce preterm birth in high-risk patients, is offered to patients as a personal therapy attempt. The aim of this study was to evaluate determinants related to pregnancy, including PETN intake during pregnancy, on immediate neonatal outcomes in a cohort of growth-restricted infants born before 32 completed weeks of gestation. Methods We performed a retrospective cohort study of 98 infants born with a birth weight below the 10th percentile before 32 completed weeks of gestation at our tertiary care center between 2010 and 2019. PETN was offered to all mothers with a history of severe adverse pregnancy outcomes who were at high risk of developing fetal growth restriction as an individual therapy attempt. Results The mean gestational age at birth was 188.5 days, and the mean birth weight was 549 g, corresponding to a median percentile of three. In 73 (79.3%) cases, brain sparing occurred during pregnancy. A total of 22 (22.4%) neonates were stillborn, 20 died postnatally, and 37.3% developed a severe complication. Multivariable analysis revealed birth weight percentile, gestational age at birth, and gestational age when brain sparing first occurred to be robust predictors of mortality or severe neonatal morbidity. In 39 neonates of mothers taking PETN, this impact of brain sparing was not observed. Conclusion Our study is the first to demonstrate a significant association between the early occurrence of brain-sparing and severe neonatal outcomes in a cohort of very early preterm, growth-restricted newborns. The data suggest that PETN intake may ameliorate the effect of brain sparing in the affected neonates.